2020
DOI: 10.1186/s12934-020-01454-6
|View full text |Cite
|
Sign up to set email alerts
|

MAL62 overexpression enhances uridine diphosphoglucose-dependent trehalose synthesis and glycerol metabolism for cryoprotection of baker’s yeast in lean dough

Abstract: Background In Saccharomyces cerevisiae, alpha-glucosidase (maltase) is a key enzyme in maltose metabolism. In addition, the overexpression of the alpha-glucosidase-encoding gene MAL62 has been shown to increase the freezing tolerance of yeast in lean dough. However, its cryoprotection mechanism is still not clear. Results RNA sequencing (RNA-seq) revealed that MAL62 overexpression increased uridine diphosphoglucose (UDPG)-dependent t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…This suggested that a high glucose level increased the metabolic output of trehalose, while the addition of Ca 2+ decreased the trehalose output of yeast cells in a high‐glucose environment. Trehalose is a good yeast protector and can protect yeast cells when under stress 46 . Increased yeast trehalose content promotes the normal metabolic functioning of the yeast itself in a high‐glucose environment 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that a high glucose level increased the metabolic output of trehalose, while the addition of Ca 2+ decreased the trehalose output of yeast cells in a high‐glucose environment. Trehalose is a good yeast protector and can protect yeast cells when under stress 46 . Increased yeast trehalose content promotes the normal metabolic functioning of the yeast itself in a high‐glucose environment 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Trehalose is a good yeast protector and can protect yeast cells when under stress. 46 Increased yeast trehalose content promotes the normal metabolic functioning of the yeast itself in a high-glucose environment. 29 However, the addition of Ca 2+ may protect the activity of yeast through various antioxidant means, so that yeast has a reduced dependence on trehalose metabolism similar to that in the high glucose with Ca 2+ group for intracellular glycerol.…”
Section: Effect Of Ca 2+ Signal On Trehalose Content Of Yeastmentioning
confidence: 99%
“…The existing dates showed that genetic engineering is a potential method to improve the survival rate of bacteria during freeze-drying. As UGPase plays a highly critical role in cellular integrity, it has been overexpressed in yeast [9] , Dendrobium officinal [10] , Aureobasidium pullulans [2] , and successfully enhanced their freeze-drying tolerance. However, there is little known about the correlation between UGPase with freeze-drying tolerance of LAB.…”
Section: Introductionmentioning
confidence: 99%